CHANGES IN THE SPORTS ACHIEVEMENT FOR 5000 METERS DISTANCE RUNNING FOLLOWING NORMOBARIC HYPOXIA TRAINING - Iveta Bonova (Journal of Applied Sports Sciences)
The aim of this study is to investigate the changes in the sports achievements for 5,000 meters running as a result of interval normobaric hypoxia training. Ten college sportsmen preparing for national and students long distance track and field championships, were randomly assigned into two groups - Experimental and Control. The Experimental group performed 3 training sessions weekly with interval normobaric hypoxia. The experiment was of 6 weeks duration. Every new week the hypoxic stimulus was increased with 500 m simulated altitude while speed of running remained constant during the whole experiment. The training speed of running was determined individually as 70% from the maximal running speed at VO2 max from incremental cardio-pulmonary test to exhaustion. The control group was performing standard training at 560 m altitude. The results show statistically significant improvement (p< 0.05) in the sports results in the experimental group which improved their personal best records in 5000 m long distance. The results also show small, but significant increase in VO2 max for the Experimental group, while there is not such a tendency in the Control group